2020
DOI: 10.1002/jor.24623
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of EBRA‐cup measurements after reconstruction of severe acetabular defects at revision THR

Abstract: Radiostereometric analysis (RSA) is the most accurate method of measuring component migration using radiographs but is restricted to use in prospective studies. Ein‐Bild‐Roentgen‐analyze (EBRA)‐Cup can be used retrospectively, but its accuracy to measure component migration following revision is unknown. This study aimed to determine the accuracy of EBRA‐Cup measurements of uncemented acetabular component migration after revision total hip replacement (THR). The secondary aim was to compare the number of cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…A recently published study by Abrahams et al reported accuracy of the EBRA cup in uncemented acetabular components [38]. In addition, for EBRA cup and radiostereometric analysis (RSA) the authors reported good agreement on classification of components that migrated proximally 1 mm up or down at two years with 100% sensitivity and 87% specificity [38]. In our study, EBRA analysis showed significantly greater medial and cranial cup migration in the study group.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A recently published study by Abrahams et al reported accuracy of the EBRA cup in uncemented acetabular components [38]. In addition, for EBRA cup and radiostereometric analysis (RSA) the authors reported good agreement on classification of components that migrated proximally 1 mm up or down at two years with 100% sensitivity and 87% specificity [38]. In our study, EBRA analysis showed significantly greater medial and cranial cup migration in the study group.…”
Section: Discussionsupporting
confidence: 69%
“…To the best of our knowledge, we are the first study to date to investigate dislocation rate after liner exchange using EBRA measurements for wear and cup migration. A recently published study by Abrahams et al reported accuracy of the EBRA cup in uncemented acetabular components [38]. In addition, for EBRA cup and radiostereometric analysis (RSA) the authors reported good agreement on classification of components that migrated proximally 1 mm up or down at two years with 100% sensitivity and 87% specificity [38].…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, EBRA is a suitable method for identifying and measuring the migration behavior of THA components [9,17,18]. While roentgen stereometric analysis (RSA) is considered the gold standard for migration measurements, Abrahams et al [10] recently reported good agreement between EBRA cup and RSA measurements of migration of acetabular cups in THA. Knowing that and applying a retrospective study design, we used EBRA cup software for our investigations of migration behavior.…”
Section: Discussionmentioning
confidence: 99%
“…ball markers) [9]. EBRA has a proven accuracy and sensitivity in detecting migration of more than 1 mm as compared to RSA (roentgen stereophotogrammetric analysis) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…As tantalum balls must be implanted, this type of migration analysis involves a major effort and cannot be performed retrospectively [30,32,33]. Abraham showed that EBRA can accurately measure migration of uncemented acetabular components used at revision THA [34] and that EBRA cup and RSA measurements had a good agreement on the classification of components above and below 1 mm at 2 years with a sensitivity and specificity of 100% and 87%, respectively [34]. In cases of pelvic discontinuity and the use of augments and cages, the accuracy of EBRA migration measurements was significantly poorer [34].…”
Section: Discussionmentioning
confidence: 99%